2012
DOI: 10.1016/j.cognition.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving enduring spatial representations after disorientation

Abstract: Four experiments tested whether there are enduring spatial representations of objects’ locations in memory. Previous studies have shown that under certain conditions the internal consistency of pointing to objects using memory is disrupted by disorientation. This disorientation effect has been attributed to an absence of or to imprecise enduring spatial representations of objects’ locations. Experiment 1 replicated the standard disorientation effect. Participants learned locations of objects in an irregular la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These findings support the idea that the two forms of representations are partially dissociable in humans, but suggest that both develop in parallel during learning. See also [16, 3133] for similar conclusions.…”
mentioning
confidence: 55%
“…These findings support the idea that the two forms of representations are partially dissociable in humans, but suggest that both develop in parallel during learning. See also [16, 3133] for similar conclusions.…”
mentioning
confidence: 55%
“…In this framework, egocentric encoding is naturally coupled with reaching space and short‐term retrieval, while allocentric encoding is coupled with navigation and long‐term retrieval, as predicted by the neuro‐computational model of Byrne, Becker and Burgess () and by other authors (e.g. Li et al ., ; Waller & Hodgson, ). In line with this, Piccardi et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies reporting executive functions as the main determinant of navigation skills in childhood (Purser, Farran, Courbois, Lemahieu, Mellier, Sockeel & Blades, ). In other words, school‐age children are not yet able to switch between and/or simultaneously use different reference frames and sources of spatial information depending on task requirements, as it is accomplished, instead, by fully developed individuals (reviewed in Burgess, ; see also Burgess et al ., ; Lafon, Vidal & Berthoz, ; Li, Mou & McNamara, ; Mou, McNamara & Zhang, ; Waller & Hodgson, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, place cell firing is not controlled by a configuration of proximal objects within an environment (Cressant et al, ). Human behavioral studies have suggested that configurations of objects can serve as an allocentric frame of reference (Mou et al, ; Li et al, ; Mou and Zhou, ). Nevertheless, encoding relative to geometric boundaries seems to be superior to encoding relative to landmarks (Cheng and Newcombe, ).…”
Section: Discussionmentioning
confidence: 99%